The effectiveness of couple therapy based on schema and ACT on marital boredom and emotion regulation in nurses with marital conflicts - Deldadeh mehraban , Mina; Hasanzadeh , Ramezan; Karimi , Ramin (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The aim of this study was to compare the effectiveness of schema-based couple therapy approach and act on marital boredom, emotion regulation in nurses with marital conflicts. Method: The present research method is experimental. The research design is quasi-experimental with pre-test-post-test design and one-month follow-up with the control group. The statistical population included all nurses serving in Imam Sajjad Government Hospital in Ramsar in 2020. Among them, 30 couples (90 people) were selected by available non-random sampling method and were replaced in the experimental group (couple therapy based on schema and act) and a control group by simple random sampling (15 couples in each group). Then, 10 90-minute sessions (2 sessions per week) of schema and act-based couple therapy (Leo and McKee, 2017) were performed in experimental groups. Data were collected using the Sanai and Barati Marital Conflict Questionnaire (2000), the Pines Marital Boredom Questionnaire (1996) and the Gross and John Emotion Regulation Questionnaire (2003). Data were analyzed using SPSS-24 software and repeated measures analysis of variance. Results: The results showed that schema-based couple therapy based on marital boredom (P<0.001, F=13.53) and emotion regulation (P<0.001, F=49.86) in nurses with Marital conflicts are effective. Conclusion: Considering the effectiveness of couple therapy based on schema and act in nurses with marital conflicts, it is recommended that therapists use this therapeutic and educational approach.